Affecting Factors Utilization of Mom and Child Health Book by Mothers of 6 Years Old Children in Baktiraja Puskesmas - Fransiska Debata Raja; Nova Sontry Node Siregar; Debora Simamora; Glorya Tambunan; Benny Maria Lumbantoruan (Sean Institute, 2025)
The results of this study indicate that mothers who have children aged 6 years make good use of MCH books by 41.4%, have good knowledge of 63.8%, have a positive attitude towards the use of MCH books by 48.3%, get good support from officers health by 48.3% and those who received good support from the closest family were 44.8%. Based on the analysis, there was no relationship between mother's knowledge and the use of MCH books (p=0.382), there was a relationship between mother's attitude and the use of MCH books (p=0.034), there was a relationship between health worker support and MCH book use (p=0.017) and closest family to the use of MCH handbooks (p=002).